Optimization of Newcastle disease virus production in T-flask - Arifin, Mohd Azmir; Mel, Maizirwan; Salim, Siti Hajar; Abdul Karim, Mohd Ismail; Hassan, Sharifah Syed (Academic Journals, 2011)
Newcastle disease (ND) is regarded as one of the most important diseases in the poultry industry. Currently, vaccines for ND are produced by using embryonated chicken eggs, a method which has the disadvantages of being labour-intensive, time consuming and requires large area for the incubation of eggs. In the present study, the production of lentogenic Asplin F strain of Newcastle disease virus by using cell culture method was studied. Experiments were carried out in T-flasks to investigate the effects of serum concentration in the culture medium during virus replication phase and multiplicity of infection (MOI) on ND virus propagation in DF-1 cells. Results show that virus infectivity titre of 6.62 x 107 TCID50/ml was achieved when serum concentration of 0.5% and MOI of 20 was used